2006
DOI: 10.1097/01.blo.0000224000.87517.4c
|View full text |Cite
|
Sign up to set email alerts
|

Migration Pattern of a Short Femoral Neck Preserving Stem

Abstract: Therapeutic Level IV. See The Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
3
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 23 publications
5
47
3
2
Order By: Relevance
“…In our study we did not observe radiological signs of migration, and no patient complained about thigh pain at the time of follow-up. Other study groups found some early retroversion of the CFP stem that stabilised one year after surgery [8].…”
Section: Discussionmentioning
confidence: 99%
“…In our study we did not observe radiological signs of migration, and no patient complained about thigh pain at the time of follow-up. Other study groups found some early retroversion of the CFP stem that stabilised one year after surgery [8].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are of clinical relevance as the association between reconstruction and implant failure is well understood but longer follow ups for short stems are still rare [19,20]. In a RSA migration study Röhrl et al [21], reported on the twoyear results of a short femoral component and concluded that the low migration would suggest a favourably long-term outcome. Lombardi et al [22] published the promising results for a short tapered stem at a mean followup of 7.3 months.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, the implantation of a neck-preserving stem has been shown to generate less contact stress on the medial cortex, than a neck resecting implant [9]. Finally, migration studies have reported that preserving the femoral neck reduces distal migration of the femoral stem [26,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Reported complications of the CFP stem include undersizing of the stem intra-operatively, recurrent dislocation due to low femoral neck osteotomy, displacement of the stem collar and early retroversion of the stem [42]. The incidence of thigh pain, which can suggest stem micro-motion, has been reported as 0% to 14% [6,39], with one series reporting a residual limp in 9% [31].…”
Section: The Collum Femoris-preserving Stemmentioning
confidence: 99%